Risk Factors of Death in the Decision to Install Artificial Intelligence Systems in the Management of Diabetes - Asbath; Kusumawati, Prima Dewi; Weraman, Pius; Sabrifha, Eli; Fauzi, Ahmad Zil (International Journal of Public Health Excellence (IJPHE), 2024)
Diabetes represents a significant public health concern, affecting millions of individuals worldwide. Its prevalence is increasing, driven in part by lifestyle factors and the aging of the global population. This systematic review explores the potential of artificial intelligence (AI) in enhancing diabetes prevention, diagnosis, and management. The review highlights the promise of personalized and proactive healthcare enabled through AI. The research methodology employed an exhaustive review of the literature, the formulation of specific inclusion and exclusion criteria, a data extraction process from selected studies that focused on the role of AI in diabetes, and a comprehensive analysis to identify the specific domains and functions in which AI makes a significant contribution. The results of the conducted literature review indicate that artificial intelligence (AI) can be regarded as a transformative force in the following eight key areas within the field of diabetes care: 1) Management and Care of Diabetes, 2) Diagnostic and Imaging Technologies, 3) Health Monitoring Systems, 4) Development of Predictive Models, 5) Public Health Interventions, 6) Lifestyle and Dietary Management, 7) Enhancement of Clinical Decision Making, and 8) Engagement and Self-Management of Patients. Additionally, the utilization of AI may result in a reduction in the risk of mortality from diabetes.